Determinants of Small-Scale Irrigation Practices in Geray Irrigation Scheme, Northwest Ethiopia - Mengistie, Demsew; Debie, Ermias (Ethiopian Journal of Social Sciences, 2020)
Developing irrigation agriculture is a means of increasing food production and of improving the livelihood of smallholder farmers dwelling in areas with very erratic and unpredictable weather conditions. Therefore, this study aimed to analyze the determinants of small irrigation practices and their contribution to household farm income in the Geray irrigation scheme in Northwest Ethiopia. A simple random sampling technique was employed for the selection of 231sample households. Data was collected from 171 irrigation users and 60 non-users. A structured household survey questionnaire, key informant interview, and focus group discussion were employed to collect primary data. Descriptive and inferential statistics were employed to estimate determinants of small-scale irrigation practice and household income. The study revealed that practicing in small-scale irrigation has played a significant role in increasing the total income of households in the study area. The study showed that practicing irrigation schemes has a positive impact on crop production. The binary logistic regression results also revealed that practicing irrigation is determined by the total income of households, livestock ownership age, family size, training, marital status, size of irrigable land, and access to market information. Therefore, to improve irrigation practices by smallholder farmers, local governments and other concerned bodies should attempt to address those factors that can affect small-scale irrigation practices in the study area.